Martyrs and archangels : Coptic literary texts from the Pierpont Morgan Library - Müller, Matthias, 1971-; Uljas, Sami.; Archelaus, of Neapolis; Archelaus, of Neapolis (Tübingen, Germany : Mohr Siebeck, 2019)
Der vorliegende Band enthält philologische Editionen dreier bisher unveröffentlichter koptischer Texte mit kommentierten Übersetzungen und Indizes. Zwei der drei Texte sind Erzählungen über Martyrien, einer ist eine Predigt über den Erzengel Gabriel.
List of Biblical and Other Textual ReferencesNames (Personal, ethnic & toponyms); Lexical Index; Loan Words; Coptic Words; Grammatical Index; Verbal Predication Patterns; Bipartite Patterns; Tripartite Patterns; Further Patterns; Clause Conjugations; Non-Verbal Sentence Patterns; Bibliography; Subject Index
eBooks on EBSCOhost
Keywords: Pierpont Morgan Library; Pierpont Morgan Library; Archangels -- Early works to 1800.; Christian martyrs -- Early works to 1800.; Coptic language -- Texts; Archanges -- Ouvrages avant 1800.; Martyrs chrétiens -- Ouvrages avant 1800.; Copte (Langue) -- Textes; Archangels; Christian martyrs; Coptic language; Early works; Texts